Motivations for Chinese Language Learning in Vietnam: From Cultural Curiosity to Career Goals: Motivations for Chinese Language Learning in Vietnam - Toan Khoa Vu Le (Faculty of Engineering, Universitas Negeri Yogyakarta, 2025)
Vietnam’s deepening integration into the global economy—marked by milestones such as the Đổi Mới reforms, accession to ASEAN and the WTO, and growing trade with China and Taiwan—has intensified demand for Chinese-speaking professionals. In this context, Chinese proficiency has emerged as valuable linguistic capital, shaping both employability and cultural engagement. This study examines the motivations driving Vietnamese university students in Ho Chi Minh City to pursue Chinese language studies, situating their learning within broader socio-economic and cultural dynamics. Grounded in Self-Determination Theory (SDT) and complemented by Dörnyei and Ottó’s Process Model of L2 Motivation, the research adopts a qualitative approach. From June 2024 to July 2025, semi-structured interviews were conducted with 29 Chinese language majors (aged 19–21) from multiple universities. Findings reveal a multidimensional motivational structure combining intrinsic cultural interest—such as appreciation for Chinese art, history, cuisine, and heritage—with extrinsic career-oriented goals, including employment in foreign-invested enterprises and scholarship opportunities. Students demonstrating integrated regulation or intrinsic motivation sustained higher engagement through self-directed study, participation in Chinese clubs, and consistent practice. However, external constraints, notably part-time work and time limitations, often hindered learning intensity. The study underscores that the quality and self-determination of motivation are as critical as its presence. Effective educational strategies should integrate cultural enrichment, practical career pathways, and learner autonomy to foster sustained commitment and maximize language acquisition outcomes.